Evaluating Teaching Material Needs for Active Adults in West Java: A Study on Cholesterol, Blood Sugar, and Uric Acid Examinations - Nursiswati; Deasy Silvya Sari; Acob, Joel Rey (Journal Of Nursing Practice, 2024)
Background: West Java is the province with the highest number of productive age population in Indonesia. The productivity of this age group is significantly influenced by health and education factors, with health teaching materials serving as educational tools. Among the challenges that hinder the productivity of active adults, chronic disease poses a significant threat. Purpose: This study aimed to describe the cholesterol, blood sugar, and uric acid examinations in active adults, including the need for health teaching materials. Method: The sampling method used was purposive sampling, with inclusion criteria being active adults aged 18 to 60 years, who work or study at an educational institution in Bandung Regency. Meanwhile, adults with mental illness were excluded, resulting in a sample size of 70 participants. The method for checking cholesterol, blood sugar, and uric acid used a Glucose Cholesterol Uric acid (GCU) meter. Results: The results showed that 12 adults had high cholesterol levels, while 6 had elevated blood sugar and uric acid levels. In the young age group (aged 18-44 years), 2 adults experienced hypercholesterolemia. The most sought-after teaching material for chronic disease was preventing sugar intake in soft drinks and the benefits of enhancing a healthy lifestyle through education. Furthermore, establishing prevention programs in educational institutions is an essential requirement to prevent the development of chronic and safeguard the productivity of active adults. Conclusions: Based on the results, it was recommended that productive and active adults receive training in chronic disease awareness and facilitate regular general check-ups (GCUs). This proactive approach was expected to contribute to the development and health security of the country.